UMER CHAPRA CONTRIBUTION IN BUILDING MUSLIM CIVILIZATION - Farida, Umma (ADDIN, 2017)
The idea of Umer Chapra in building Muslim civilization was based on his research on the position of Muslims who from time to time more and more felt strange with the civilization and Islamic values itself, even the civilization was gradually increasingly eroded and marginalized by Western culture. He tried to restore the Muslim position which should be done as the Messenger of Allah had pointed out, and their positive role in building civilization. The Islamic civilization has the power that lies in the development of morals and material strength. For Chapra, the moral development without being integrated with the economic development cannot be realized. And at the same time, this economic development must also have a worldview and strategy that is in line with religious objectives (maqashid asy-syari’ah). The development of Muslim civilization requires the transformation of human beings and their institutions, focusing in the increasing of education and personality development, and the simultaneous mobilization of material, economic and technological resources for the rearrangement of community structures over the principles of deliberation and accountability, unity, independence and justice.